PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PROFITABILITAS PERUSAHAAN (Studi Empiris pada Perusahaan Peserta Corporate Governance Perception Index (CGPI) Tahun 2012) - Wicaksono, Tangguh; Raharja, Raharja (Faculty of Economics and Business Diponegoro University, 2014)
The purpose of this study is to determine whether the GCG (GCG) has a significant effect on the profitability of the company. GCG in this case is proxiedÂ with the size of the board of directors, board of comissioner and audit committee. While the profitability variable is proxied by ROE (Return On Equity).The population of this research is companies listed in Corporate Governance Perception Index (CGPI) in 2012. Total observation of this study is 58 companies. Sampling technique using purposive sampling method. Data analysis techniques performed by hypothesis testing using multiple linear regression or OLS (Ordinary Least Square).Â Based on the survey results revealed that corporate governance variables do not have significant impact to the profitability of the company.